Composite fiber membrane adsorbent as well as preparation method and application thereof
By coating the manganese lithium ion sieve with carbon material and loading it on the polymer fiber membrane, the problem of easy structure damage in manganese lithium ion sieve under acidic conditions is solved, and the effect of high adsorption capacity and low manganese dissolution is achieved, and its circulating lithium extraction performance is improved.
Patent Information
- Application Number
- CN202411695133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
AI Technical Summary
The structure of manganese lithium ion sieve is easily damaged when desorbed under acidic conditions, resulting in the dissolution loss of manganese elements and attenuation of adsorption capacity. The molding problem has not been completely solved, affecting its large-scale commercial application.
Using composite fiber membrane adsorbent, the stability and adsorption capacity of the manganese-based lithium-ion sieve coated carbon material on the polymer fiber membrane are improved by loading it onto the polymer fiber membrane.
It effectively reduces manganese dissolution, improves adsorption capacity and stability, and significantly improves the circulating lithium extraction performance of manganese-based lithium ion sieve.
Smart Images

Figure CN119633769A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium resource extraction, and in particular to a composite fiber membrane adsorbent and a preparation method and application thereof. Background Art
[0002] Although the technology of extracting lithium from salt lake brine and underground brine has developed a variety of processes such as precipitation, extraction and calcination, these methods face many limitations due to low lithium recovery rate, high cost and significant negative impact on the environment. In contrast, the adsorption method is gradually becoming an important direction of technological innovation in this field due to its selective adsorption capacity for lithium ions, environmental friendliness, high resource utilization efficiency, large adsorption capacity, economic feasibility and reusability.
[0003] The most common manganese-based lithium ion sieves in the adsorption method include MnO2·0.3H2O, MnO2·0.5H2O, etc. These manganese-based lithium ion sieves have excellent lithium ion adsorption selectivity and high adsorption capacity, and show great potential in the application of lithium extraction from brine. However, this type of manganese-based lithium ion sieve still has some problems that need to be solved in practical applications. For example, when desorbed under acidic conditions, the structure of the manganese-based lithium ion sieve will be destroyed, causing the dissolution loss of manganese elements, resulting in a significant attenuation of its adsorption capacity. Moreover, the molding problem of manganese-based lithium ion sieves has not been completely solved, and there is often no balance between granulation molding and maintaining high adsorption capacity. These problems have limited the progress of large-scale commercial application of manganese-based lithium ion sieves.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a composite fiber membrane adsorbent and a preparation method and application thereof, aiming to reduce the manganese dissolution loss of manganese-based lithium ion sieves during the desorption process, increase the contact area with the lithium-containing solution, and thereby improve the adsorption capacity and stability of the manganese-based lithium ion sieves.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a composite fiber membrane adsorbent, comprising a polymer fiber membrane and a manganese-based lithium ion sieve-coated carbon material supported on the polymer fiber membrane.
[0007] In an optional embodiment, the carbon material in the manganese-based lithium ion sieve-coated carbon material includes carbon nanotubes; And / or, the manganese-based lithium ion sieve in the manganese-based lithium ion sieve-coated carbon material has a spinel-type crystal structure; And / or, the manganese-based lithium ion sieve in the manganese-based lithium ion sieve-coated carbon material includes a Z element, the Z element includes at least one of aluminum and cobalt, and the molar ratio of the Z element to the manganese element is 0.001-0.05:1; And / or, the polymer in the polymer fiber membrane includes at least one of polyvinyl chloride, polyvinylidene chloride and polyvinylidene fluoride.
[0008] In a second aspect, the present invention provides a method for preparing the composite fiber membrane adsorbent as described in the first aspect, comprising the following steps: S1, dispersing the carbon material into a first acid solution for pretreatment to obtain a pretreated carbon material; a manganese source, a lithium source and a Z source undergo a hydrothermal reaction and a first calcination to obtain a manganese-based lithium ion sieve precursor; S2, mixing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent for the first time, filtering, and subjecting the obtained solid to the second calcination to obtain a manganese-based lithium ion sieve precursor-coated carbon material; S3, dispersing the manganese-based lithium ion sieve precursor coated carbon material into a polymer solution, and spinning the mixture to obtain a composite fiber membrane adsorbent precursor; S4, treating the composite fiber membrane adsorbent precursor in a second acid solution to obtain the composite fiber membrane adsorbent.
[0009] In an optional embodiment, the first acid solution is a mixed solution of hydrochloric acid and sulfuric acid, and the volume ratio of hydrochloric acid to sulfuric acid is 1:2-5.
[0010] In an optional embodiment, the first mixing includes ultrasonically dispersing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent respectively to obtain a pretreated carbon material suspension and a manganese-based lithium ion sieve precursor suspension, and dropwise adding the manganese-based lithium ion sieve precursor suspension into the pretreated carbon material suspension.
[0011] In an optional embodiment, S1 satisfies at least one of the following conditions (1) to (5): Condition (1): The pretreatment includes heating to 100°C to 130°C and stirring for 2h to 4h, followed by filtering, washing and drying; Condition (2): The Z source includes at least one of an aluminum source and a cobalt source, and the molar ratio of the Z element in the Z source to the manganese element in the manganese source is 0.001-0.05:1; Condition (3): A pore-forming agent is further added to the hydrothermal reaction, wherein the pore-forming agent comprises at least one of ammonium carbonate and ammonium bicarbonate, and the mass of the pore-forming agent accounts for 10% to 30% of the total mass of the manganese source, the lithium source and the Z source; Condition (4): The temperature of the hydrothermal reaction is 110°C to 180°C and the duration is 30h to 55h; Condition (5): The temperature of the first calcination is 400°C to 550°C, and the duration is 6h to 12h.
[0012] In an optional embodiment, S2 satisfies at least one of the following conditions (6) to (8): Condition (6): The mass ratio of the first mixture of the pretreated carbon material and the manganese-based lithium ion sieve precursor is 0.1-0.6:1; Condition (7): The temperature of the second calcination is 400°C to 600°C, and the duration is 2h to 8h; Condition (8): The second calcination is carried out under a protective atmosphere.
[0013] In an optional embodiment, S3 satisfies at least one of the following conditions (9) to (11): Condition (9): The polymer comprises at least one of polyvinyl chloride, polyvinylidene chloride and polyvinylidene fluoride, and the concentration of the polymer solution is 55 g / L to 75 g / L; Condition (10): The mass ratio of the manganese-based lithium ion sieve precursor coated carbon material to the polymer is 1:0.1-0.2; Condition (11): The spinning process further includes drying, the drying temperature is 60° C.-90° C., and the drying time is 24 h-72 h.
[0014] In an optional embodiment, the second acid solution includes hydrochloric acid with a concentration of 0.1 mol / L to 0.5 mol / L.
[0015] In a third aspect, the present invention provides a use of the composite fiber membrane adsorbent provided in the first aspect or the composite fiber membrane adsorbent prepared by the preparation method provided in the second aspect in extracting lithium from brine.
[0016] The present invention has the following beneficial effects: (1) The present invention relates to a composite fiber membrane adsorbent, which uses a manganese-based lithium ion sieve coated carbon material as a lithium extraction active substance, and further loads the lithium extraction active substance on a polymer fiber membrane. The one-dimensional structure of the nano-carbon material has a large specific surface area, so that the manganese-based lithium ion sieve coated on its surface also has a high specific surface area. Therefore, the manganese-based lithium ion sieve particles will not agglomerate and can fully contact with the lithium-containing solution, thereby improving the adsorption rate and adsorption capacity. The manganese-based lithium ion sieve is doped with Z element, which is beneficial to reduce the Mn in the manganese-based ion sieve. 3+ The disproportionation reaction and Jahn-Teller effect effectively reduce manganese dissolution loss and improve the stability of the crystal structure of the manganese ion sieve. Therefore, the composite fiber membrane adsorbent prepared by the present invention has high adsorption capacity and low manganese dissolution loss, and exhibits excellent cyclic lithium extraction performance.
[0017] (2) The present invention pre-treats the carbon material with an acid solution, thereby reducing impurities on the surface of the carbon material and increasing the hydrophilic groups and electrostatic attraction on the surface. This not only improves the dispersibility, but also promotes the attachment of the manganese-based lithium ion sieve precursor to the surface of the carbon material. Further, the manganese-based lithium ion sieve precursor is tightly coated on the carbon material by high-temperature calcination, ensuring the stability of the coating structure during long-term lithium extraction. Finally, the manganese-based lithium ion sieve precursor coated carbon material is loaded on a polymer fiber membrane by a spinning molding technology, and after acid leaching and lithium removal, a composite fiber membrane adsorbent that is convenient for industrial application is formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a scanning electron microscope image of the composite fiber membrane adsorbent prepared in Example 1; Figure 2 This is the X-ray diffraction pattern of the composite fiber membrane adsorbent prepared in Example 1. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.
[0021] In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0022] In the description of the embodiments of the present application, the terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order, or primary and secondary relationship of the indicated technical features. The term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone.
[0023] For simplicity, the present invention specifically discloses some numerical ranges, and various numerical ranges can be combined with each other to form corresponding embodiments. The endpoints and any value of the scope disclosed in the present disclosure are not limited to this accurate scope or value, and these scopes or values should be understood as comprising values close to these scopes or values. For numerical range, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between the separate point value, can be combined with each other and obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0024] Unless otherwise specified, the terms used in the present invention have the commonly understood meanings that are generally understood by those skilled in the art.
[0025] The following is a detailed description of a composite fiber membrane adsorbent provided by the present invention, and its preparation method and application.
[0026] At present, due to its own structural reasons, manganese dissolution occurs in manganese-based lithium ion sieves during acid leaching and lithium extraction, resulting in a significant decrease in its adsorption capacity during long-term lithium extraction, affecting the lithium extraction efficiency. In order to solve the above technical problems, the present invention proposes the following technical solutions.
[0027] The invention provides a composite fiber membrane adsorbent, comprising a polymer fiber membrane and a manganese-based lithium ion sieve-coated carbon material loaded on the polymer fiber membrane.
[0028] In some embodiments, the manganese-based lithium ion sieve-coated carbon material refers to a material having a carbon material as a core and a manganese-based lithium ion sieve coating layer on the surface of the carbon material, wherein the manganese-based lithium ion sieve is a lithium extraction material.
[0029] In some embodiments, the carbon material includes carbon nanotubes. The carbon material used in the present invention is a one-dimensional nanomaterial with a high specific surface area, so that the manganese-based lithium ion sieve coated on its surface also has a high specific surface area, which can be fully contacted with the lithium-containing solution to improve the efficiency of lithium extraction. At the same time, the carbon material has good chemical stability, does not react during the acid leaching process, and can maintain the structural stability of the overall material.
[0030] In some embodiments, the manganese-based lithium ion sieve includes a Z element, the Z element includes at least one of aluminum and cobalt, and the molar ratio of the Z element to the Mn element is 0.001 to 0.05: 1. By doping the manganese-based lithium ion sieve with elements, the manganese content is reduced, the dissolution loss of manganese is reduced, and the stability of the lithium ion sieve is improved.
[0031] In some embodiments, the polymer in the polymer fiber membrane includes at least one of polyvinyl chloride, polyvinylidene chloride, and polyvinylidene fluoride.
[0032] Accordingly, the present invention provides a method for preparing a composite fiber membrane adsorbent, comprising the following steps: S1. Dispersing the carbon material into a first acid solution for pretreatment to obtain a pretreated carbon material; placing a manganese source, a lithium source and a Z source in a reaction kettle according to a stoichiometric ratio, and performing a hydrothermal reaction and a first calcination to obtain a manganese-based lithium ion sieve precursor (Z-LMO).
[0033] In some embodiments, the present invention does not limit the preparation order of the pretreated carbon material and the manganese-based lithium ion sieve precursor. The pretreated carbon material can be prepared first, or the manganese-based lithium ion sieve precursor can be prepared first, or the pretreated carbon material and the manganese-based lithium ion sieve precursor can be prepared at the same time.
[0034] In some embodiments, the carbon material includes carbon nanotubes.
[0035] In some embodiments, the first acid solution is a mixed solution of hydrochloric acid and sulfuric acid, and the volume ratio of hydrochloric acid to sulfuric acid is 1:2-5, for example, it can be any one of 1:2, 1:3, 1:4, 1:5 or a range value between any two of them.
[0036] In some embodiments, the solid-liquid ratio of the carbon material to the first acid solution is 1 g: 10 mL to 30 mL.
[0037] In some embodiments, the pretreatment includes heating to 100°C to 130°C and stirring for 2h to 4h, followed by filtering, washing, and drying. The heating temperature for the pretreatment can be any one of 100°C, 110°C, 120°C, and 130°C, or a range between any two thereof; the heating time for the pretreatment can be any one of 2h, 3h, and 4h, or a range between any two thereof.
[0038] Dispersing the carbon material in the first acid solution for treatment reduces impurities on the carbon material surface, lowers the aspect ratio, makes it less likely to agglomerate, improves dispersion performance, and increases its surface hydrophilic groups and electrostatic attraction.
[0039] In some embodiments, the manganese-based lithium ion sieve precursor (Z-LMO) is a Z-element doped lithium manganese oxide having a spinel crystal structure.
[0040] In some embodiments, the manganese source includes at least one of nano-sized Mn2CO3, Mn2O3, MnO2, and Mn3O4, and the lithium source includes at least one of LiOH, LiOH·H2O, LiCl, and Li2CO3. The Z source includes at least one of an aluminum source and a cobalt source, wherein the aluminum source includes at least one of AlF3 and Al2O3, and the cobalt source includes at least one of CoCl2, CoSO4, Co(NO3)2, and CoCO3.
[0041] In some embodiments, the molar ratio of the Z element in the Z source to the manganese element in the manganese source is 0.001 to 0.05:1, for example, it can be any one of 0.001:1, 0.005:1, 0.01:1, 0.03:1, 0.05:1, or a range value between any two of them. Doping lithium manganese oxide with the Z element can reduce the presence of manganese in the lithium manganese oxide, thereby reducing the dissolution of manganese and improving the lattice stability of the manganese-based lithium ion sieve. If the molar ratio of the Z element to the manganese element is too large, the spinel structure of the manganese-based lithium ion sieve will be destroyed, thereby reducing the adsorption capacity. If the molar ratio of the Z element to the manganese element is too small, it will result in insufficient modification and will not be able to effectively reduce manganese dissolution loss.
[0042] In some embodiments, a pore former is further added to the hydrothermal reaction, and the pore former includes at least one of ammonium carbonate and ammonium bicarbonate, and the mass of the pore former accounts for 10% to 30% of the total mass of the manganese source, the lithium source and the Z source, for example, it can be any one of 10%, 20%, 30% or a range value between any two of them.
[0043] Introducing a pore-forming agent into the hydrothermal reaction creates pores in the resulting manganese-based lithium ion sieve precursor, which can increase the specific surface area of the material and thereby increase the contact area with the lithium-containing solution, thereby improving the lithium extraction efficiency.
[0044] In some embodiments, the temperature of the hydrothermal reaction is 110° C. to 180° C., for example, it can be any one of 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., or a range between any two thereof. The duration of the hydrothermal reaction is 30 h to 55 h, for example, it can be any one of 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, or a range between any two thereof.
[0045] In some embodiments, the temperature of the first calcination is 400°C to 550°C, for example, it can be any one of 400°C, 450°C, 500°C, 550°C, or a range between any two of them; the duration of the first calcination is 6h to 12h, for example, it can be any one of 6h, 8h, 10h, 12h, or a range between any two of them.
[0046] In some embodiments, after the hydrothermal reaction is completed, filtering, washing, drying, and then a first calcination is performed.
[0047] S2, mixing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent for the first time, filtering, and subjecting the obtained solid to the second calcination to obtain the manganese-based lithium ion sieve precursor coated carbon material.
[0048] In some embodiments, the first mixing includes ultrasonically dispersing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent to obtain a pretreated carbon material suspension and a manganese-based lithium ion sieve precursor suspension; and dripping the manganese-based lithium ion sieve precursor suspension into the pretreated carbon material suspension. The solvent includes ethanol.
[0049] In some embodiments, the present invention does not limit the preparation order of the pretreated carbon material suspension and the manganese-based lithium ion sieve precursor suspension. The pretreated carbon material suspension can be prepared first, or the manganese-based lithium ion sieve precursor suspension can be prepared first, or the pretreated carbon material suspension and the manganese-based lithium ion sieve precursor suspension can be prepared at the same time.
[0050] In some embodiments, the mass ratio of the first mixture of the pretreated carbon material and the manganese-based lithium ion sieve precursor is 0.1-0.6:1, for example, it can be any one of 0.1:1, 0.3:1, 0.6:1 or a range value between any two of them.
[0051] The manganese-based lithium ion sieve precursor suspension is added dropwise to the pretreated carbon material suspension. Due to the hydrophilic groups and electrostatic attraction on the surface of the pretreated carbon material, when the manganese-based lithium ion sieve precursor and the pretreated carbon material come into contact, the manganese-based lithium ion precursor is attracted by the surface of the pretreated carbon material and adheres to its surface.
[0052] In some embodiments, the temperature of the second calcination is 400°C~600°C, for example, it can be any one of 400°C, 500°C, 600°C or a range between any two of them; the duration of the second calcination is 2h~8h, for example, it can be any one of 2h, 4h, 6h, 8h or a range between any two of them.
[0053] In some embodiments, the second calcination is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium and argon. After the second calcination, the manganese-based lithium ion sieve precursor is tightly coated on the carbon material to form a manganese-based lithium ion sieve precursor coated carbon material.
[0054] S3. Dispersing the manganese-based lithium ion sieve precursor coated carbon material into a polymer solution, and spinning the mixture to obtain a composite fiber membrane adsorbent precursor.
[0055] In some embodiments, the polymer includes at least one of polyvinyl chloride, polyvinylidene chloride and polyvinylidene fluoride, and the concentration of the polymer solution is 55 g / L to 75 g / L, for example, it can be any one of 55 g / L, 65 g / L, 75 g / L or a range between any two of them. If the concentration of the polymer solution is too high, the diameter of the prepared fiber will increase and the specific surface area will decrease, thereby affecting the adsorption of the manganese-based lithium ion sieve; if the concentration of the polymer solution is too low, the molding effect will be poor and it will be difficult to apply in practice.
[0056] In some embodiments, the mass ratio of the carbon material coated with the manganese-based lithium ion sieve precursor to the polymer is 1:0.1-0.2, for example, it can be any one of 1:0.1, 1:0.15, 1:0.2, or a range between any two of them. If the mass ratio of the carbon material coated with the manganese-based lithium ion sieve precursor to the polymer is too high, the lithium extraction active substance is too much embedded in the polymer fiber membrane, and the adsorption capacity is reduced; if the mass ratio is too low, the sample molding is affected, which is not conducive to long-term use.
[0057] In some embodiments, the spinning process includes spraying a polymer solution dispersed with a manganese-based lithium ion sieve precursor coated carbon material into a coagulation bath through a spinning device for solidification and forming. The coagulation bath is an ethanol solution with a concentration of 40% to 80%.
[0058] In some embodiments, the spinning process also includes drying, and the drying temperature is 60°C~90°C, for example, it can be any one of 60°C, 70°C, 80°C, 90°C or a range value between any two of them; the drying time is 24h-72h, for example, it can be any one of 24h, 36h, 48h, 50h, 72h or a range value between any two of them.
[0059] S4. Treat the composite fiber membrane adsorbent precursor in a second acid solution to obtain a composite fiber membrane adsorbent.
[0060] In some embodiments, the second acid solution includes hydrochloric acid having a concentration of 0.1 mol / L to 0.5 mol / L, for example, any one of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L or a range between any two of them.
[0061] The features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0062] Example 1 This embodiment provides a composite fiber membrane adsorbent, the preparation method of which includes: S1, take 20g carbon nanotubes and disperse them into 300mL of a mixed solution of hydrochloric acid and sulfuric acid with a volume ratio of 1:3 for pretreatment. After the pretreatment, the product obtained by suction filtration is washed with ethanol and pure water and dried to obtain pretreated carbon nanotubes. Take 49.35g LiOH·H2O, 102.3g Mn2O3, 0.22g CoCl2, 0.48g Al2O3 and 30g (NH4)2CO3 and grind them into a reactor, and add 150mL ethanol to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the obtained product is washed, dried, and calcined for the first time to obtain a manganese-based lithium ion sieve precursor.
[0063] Among them, the temperature of pretreatment is 110°C and the duration is 2h; the temperature of hydrothermal reaction is 150°C and the duration is 48h; the temperature of the first calcination is 450°C and the duration is 8h.
[0064] S2, take 100g of manganese lithium ion sieve precursor and 20g of pretreated carbon nanotubes and disperse them into 1000mL and 200mL of anhydrous ethanol solution respectively, and ultrasonically treat for 3h to obtain a manganese lithium ion sieve precursor suspension and a pretreated carbon nanotube suspension. The manganese lithium ion sieve precursor suspension is added dropwise to the pretreated carbon nanotube suspension and stirred for 3h, and then the solid obtained by suction filtration is washed with water, dried, and calcined for the second time under a nitrogen atmosphere to obtain a manganese lithium ion sieve precursor coated carbon nanotube.
[0065] The second calcination temperature is 450°C and the duration is 3 hours.
[0066] S3. Disperse the manganese-based lithium ion sieve precursor coated carbon nanotubes into a polyvinylidene chloride solution, spray them into a 60% ethanol solution through spinning to solidify and form, and dry them in an oven at 80°C for 24 hours to obtain a composite fiber membrane adsorbent precursor.
[0067] The concentration of the polyvinylidene chloride solution is 65 g / L, and the mass ratio of the manganese-based lithium ion sieve precursor-coated carbon nanotubes to the polyvinylidene chloride is 1:0.15.
[0068] S4. Place the composite fiber membrane adsorbent precursor in 500 mL of hydrochloric acid solution and stir for 10 hours, filter and dry to obtain the composite fiber membrane adsorbent.
[0069] Wherein, the concentration of the hydrochloric acid solution is 0.15 mol / L.
[0070] Attached Figure 1 This is a scanning electron microscope image of the composite fiber membrane adsorbent obtained in this example. It can be seen that the surface of the composite fiber membrane adsorbent is smooth, and some protrusions on the fiber are in the shape of manganese-based lithium ion sieve-coated carbon nanotubes.
[0071] Attached Figure 2 The X-ray diffraction pattern of the composite fiber membrane adsorbent obtained in this example shows that the main peak and Li 1.6 Mn 1.6 The standard PDF card of O4 corresponds to that of the manganese-based lithium ion sieve.
[0072] Example 2 This embodiment provides a composite fiber membrane adsorbent, the preparation method of which includes: S1, take 12g carbon nanotubes and disperse them into 300mL of a mixed solution of hydrochloric acid and sulfuric acid with a volume ratio of 1:2 for pretreatment. After the pretreatment, the product obtained by suction filtration is washed with ethanol and pure water and dried to obtain pretreated carbon nanotubes. Take 49.35g LiOH·H2O, 97.88g Mn2O3, 1.29g CoCl2, 1.01g Al2O3 and 30g (NH4)2CO3 and grind them into a reactor, and add 150mL ethanol to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the obtained product is washed, dried, and calcined for the first time to obtain a manganese-based lithium ion sieve precursor.
[0073] Among them, the temperature of pretreatment is 100°C and the duration is 4 hours; the temperature of hydrothermal reaction is 180°C and the duration is 30 hours; the temperature of the first calcination is 400°C and the duration is 6 hours.
[0074] S2, take 120g of manganese lithium ion sieve precursor and 12g of pretreated carbon nanotubes and disperse them into 1000mL and 200mL of anhydrous ethanol solution respectively, and ultrasonically treat for 3h to obtain a manganese lithium ion sieve precursor suspension and a pretreated carbon nanotube suspension. The manganese lithium ion sieve precursor suspension is added dropwise to the pretreated carbon nanotube suspension and stirred for 3h, and then the solid obtained by suction filtration is washed with water, dried, and calcined for the second time under a nitrogen atmosphere to obtain a manganese lithium ion sieve precursor coated carbon nanotube.
[0075] The second calcination temperature is 600°C and the duration is 2h.
[0076] S3. Disperse the manganese-based lithium ion sieve precursor coated carbon nanotubes into a polyvinylidene chloride solution, spray them into an ethanol solution with a concentration of 80% through spinning to solidify them, and dry them in an oven at 60°C for 72 hours to obtain a composite fiber membrane adsorbent precursor.
[0077] The concentration of the polyvinylidene chloride solution is 58 g / L, and the mass ratio of the manganese-based lithium ion sieve precursor-coated carbon nanotubes to polyvinylidene chloride is 1:0.12.
[0078] S4. Place the composite fiber membrane adsorbent precursor in 500 mL of hydrochloric acid solution and stir for 10 hours, filter and dry to obtain the composite fiber membrane adsorbent.
[0079] Wherein, the concentration of the hydrochloric acid solution is 0.5 mol / L.
[0080] Example 3 This embodiment provides a composite fiber membrane adsorbent, the preparation method of which includes: S1, take 20g carbon nanotubes and disperse them into 300mL of a mixed solution of hydrochloric acid and sulfuric acid with a volume ratio of 1:5 for pretreatment. After the pretreatment, the product obtained by suction filtration is washed with ethanol and pure water and dried to obtain pretreated carbon nanotubes. Take 49.35g LiOH·H2O, 101.3g Mn2O3, 0.32g CoCl2, 0.25g Al2O3 and 35g (NH4)2CO3 and grind them into a reactor, and add 150mL ethanol to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the obtained product is washed, dried, and calcined for the first time to obtain a manganese-based lithium ion sieve precursor.
[0081] Among them, the temperature of pretreatment is 130°C and the duration is 3 hours; the temperature of hydrothermal reaction is 110°C and the duration is 55 hours; the temperature of the first calcination is 550°C and the duration is 6 hours.
[0082] S2, take 100g of manganese lithium ion sieve precursor and 50g of pretreated carbon nanotubes and disperse them into 1000mL and 200mL of anhydrous ethanol solution respectively, and ultrasonically treat for 3h to obtain a manganese lithium ion sieve precursor suspension and a pretreated carbon nanotube suspension. The manganese lithium ion sieve precursor suspension is added dropwise to the pretreated carbon nanotube suspension and stirred for 3h, and then the solid obtained by suction filtration is washed with water, dried, and calcined for the second time under a nitrogen atmosphere to obtain a manganese lithium ion sieve precursor coated carbon nanotube.
[0083] The second calcination temperature is 400°C and the duration is 8 hours.
[0084] S3. Disperse the carbon nanotubes coated with the manganese-based lithium ion sieve precursor into a polyvinylidene chloride solution, spray them into a 60% ethanol solution through spinning to solidify them, and dry them in an oven at 90°C for 24 hours to obtain a composite fiber membrane adsorbent precursor.
[0085] Among them, the concentration of the polyvinylidene chloride solution is 73g / L, and the mass ratio of the manganese-based lithium ion sieve precursor-coated carbon nanotubes and polyvinylidene chloride is 1:0.18.
[0086] S4. Place the composite fiber membrane adsorbent precursor in 500 mL of hydrochloric acid solution and stir for 10 hours, filter and dry to obtain the composite fiber membrane adsorbent.
[0087] Wherein, the concentration of the hydrochloric acid solution is 0.1 mol / L.
[0088] Example 4 This embodiment provides a composite fiber membrane adsorbent, which is different from Embodiment 1 only in that the volume ratio of hydrochloric acid to sulfuric acid in S1 is 1:2.5.
[0089] Example 5 This embodiment provides a composite fiber membrane adsorbent, which is different from Embodiment 1 only in that the volume ratio of hydrochloric acid to sulfuric acid in S1 is 1:4.5.
[0090] Example 6 This embodiment provides a composite fiber membrane adsorbent, which differs from Embodiment 1 only in that, in S2, 120 g of manganese-based lithium ion sieve precursor and 20 g of pretreated carbon nanotubes are dispersed in anhydrous ethanol solution respectively to obtain a manganese-based lithium ion sieve precursor suspension and a pretreated carbon nanotube suspension.
[0091] Example 7 This embodiment provides a composite fiber membrane adsorbent, which differs from Embodiment 1 only in that, in S2, 50 g of manganese-based lithium ion sieve precursor and 20 g of pretreated carbon nanotubes are dispersed in anhydrous ethanol solution respectively to obtain a manganese-based lithium ion sieve precursor suspension and a pretreated carbon nanotube suspension.
[0092] Example 8 This embodiment provides a composite fiber membrane adsorbent, which differs from Embodiment 1 only in that, in S3, the mass ratio of the manganese-based lithium ion sieve precursor-coated carbon nanotubes to polyvinylidene chloride is 1:0.13.
[0093] Example 9 This embodiment provides a composite fiber membrane adsorbent, which differs from Embodiment 1 only in that, in S3, the mass ratio of the manganese-based lithium ion sieve precursor-coated carbon nanotubes to polyvinylidene chloride is 1:0.17.
[0094] Comparative Example 1 This comparative example provides a composite fiber membrane adsorbent, the preparation method of which includes: S1. Take 49.35g LiOH·H2O, 102.3g Mn2O3, 0.22g CoCl2, 0.48g Al2O3 and 20g (NH4)2CO3, grind them and add them into a reactor. At the same time, add 150mL ethanol to carry out hydrothermal reaction. After the hydrothermal reaction is completed, the obtained product is washed, dried and calcined for the first time to obtain a manganese-based lithium ion sieve precursor.
[0095] The temperature of the hydrothermal reaction is 150°C and the duration is 48 hours; the temperature of the first calcination is 450°C and the duration is 8 hours.
[0096] S2. Disperse the manganese-based lithium ion sieve precursor into a polyvinylidene chloride solution, spray it into a 60% ethanol solution through spinning to solidify it, and dry it in an oven at 80°C for 24 hours to obtain a composite fiber membrane adsorbent precursor.
[0097] The concentration of the polyvinylidene chloride solution is 65 g / L, and the mass ratio of the manganese-based lithium ion sieve precursor to the polyvinylidene chloride is 1:0.15.
[0098] S3. Place the composite fiber membrane adsorbent precursor in 500 mL of hydrochloric acid solution and stir for 10 hours, filter and dry to obtain the composite fiber membrane adsorbent.
[0099] Wherein, the concentration of the hydrochloric acid solution is 0.15 mol / L.
[0100] Comparative Example 2 This comparative example provides a composite fiber membrane adsorbent, which differs from Example 1 in that the carbon nanotubes are not treated with the first acid solution.
[0101] Comparative Example 3 This comparative example provides a composite fiber membrane adsorbent, which is different from Example 1 in that the pretreatment temperature in S1 is room temperature.
[0102] Comparative Example 4 This comparative example provides a composite fiber membrane adsorbent, which differs from Example 1 in that CoCl2 and Al2O3 are not added during the hydrothermal reaction of S1 to prepare the manganese-based lithium ion sieve precursor.
[0103] Comparative Example 5 This comparative example provides a composite fiber membrane adsorbent, which differs from Example 1 in that the solid obtained by filtration in S2 is not subjected to a second calcination.
[0104] Performance Testing The samples prepared in the above embodiments and comparative examples were placed in lithium-containing brine to test the lithium extraction performance. The composition of the lithium-containing brine is shown in Table 1:
[0105] (1) Adsorption capacity test: The adsorbent precursor that has not been spun into a film in the above examples and comparative examples is placed in a second acid solution for lithium removal to obtain a lithium adsorbent. The lithium adsorbent is dispersed in lithium-containing brine, the pH of the brine is adjusted to 7.5, and the amount of lithium-containing brine is continuously increased until the lithium ion concentration no longer changes, and the saturated adsorption capacity of the lithium adsorbent is calculated.
[0106] The adsorption capacity is calculated as follows: ; Among them, Q e Indicates adsorption capacity in mg / g; C0 and C e They represent the Li content of lithium-containing brine before and after adsorption. +The concentration is in mg / L; V is the volume of lithium-containing brine in L; m is the mass of lithium-extracting material in the lithium adsorbent in g. The test results are shown in Table 2.
[0107] (2) Adsorption cycle performance test: The composite fiber membrane adsorbent obtained in the above examples and comparative examples was dispersed in lithium-containing brine and stirred for adsorption for 0.75 h, with a solid-liquid ratio of 1 g: 50 mL. The adsorbed composite fiber membrane adsorbent was placed in 0.15 mol / L hydrochloric acid for desorption for 0.5 h, with a solid-liquid ratio of 1 g: 50 mL. The cycle was repeated for 200 weeks, and the adsorption capacity, adsorption capacity retention rate, adsorption rate and manganese dissolution loss were calculated.
[0108] Adsorption capacity retention rate (%) ×100%; Adsorption rate (%) = ×100%, C0 and C e They represent the Li content of lithium-containing brine before and after adsorption. + Concentration, in mg / L; Manganese dissolution loss (%) = ×100%, C1 represents the manganese content in the desorption solution, the unit is g / L; V1 represents the volume of the desorption solution, the unit is L; m0 represents the mass of manganese element in the composite fiber membrane adsorbent, the unit is g.
[0109] The above test results are shown in Table 3.
[0110] Table 2
[0111] Table 3
[0112] Combining the data in Table 2 and Table 3, the results of Examples 1-3, 6-7 and Comparative Example 1 show that the presence of carbon nanotubes and their mass ratio to the manganese-based lithium ion sieve affect the lithium extraction performance of the manganese-based lithium ion sieve. When carbon nanotubes are not added, the adsorption capacity of the manganese-based lithium ion sieve is low, and the saturated adsorption capacity is only 31.6 mg / g. This is due to the lack of high specific surface area provided by carbon nanotubes, which leads to a reduction in the contact area between the manganese-based lithium ion sieve precursor and the lithium-containing solution, thereby reducing the adsorption efficiency. In addition, a mass ratio of carbon nanotubes to the manganese-based lithium ion sieve precursor that is too large or too small will affect the adsorption capacity. If the mass ratio is too large, the relative proportion of lithium extraction materials will decrease, and the adsorption capacity will decrease; if the mass ratio is too small, the number of carbon nanotubes is insufficient to provide sufficient coating sites, and part of the manganese-based lithium ion sieve is agglomerated and cannot be fully contacted with the lithium-containing solution, and the adsorption capacity also decreases.
[0113] The results of Examples 1-5 and Comparative Examples 2-3 show that pretreatment of the carbon material with a mixed acid solution will affect the adsorption capacity of the manganese-based lithium ion sieve. If the mixed acid solution is not used for pretreatment, or the pretreatment temperature is room temperature, abundant active functional groups cannot be formed on the surface of the carbon nanotubes, resulting in that part of the manganese-based lithium ion sieve precursor cannot be effectively coated on the carbon nanotubes, but locally agglomerates, reducing the effective contact with the lithium-containing solution, thereby reducing the adsorption capacity.
[0114] The results of Examples 1 and 8-9 show that the mass ratio of carbon nanotubes coated with manganese lithium ion sieve precursor to polyvinylidene chloride affects the lithium extraction performance of the composite fiber membrane adsorbent. If the mass ratio is too high, the lithium extraction active substance is too much embedded in the polymer fiber membrane, and the adsorption capacity is reduced; if the mass ratio is too low, the sample molding is affected, which is not conducive to long-term use.
[0115] The results of Example 1 and Comparative Example 4 show that element doping has an impact on the cyclic lithium extraction performance of the composite fiber membrane adsorbent. When CoCl2 and AlO3 are not added, the manganese dissolution loss of Comparative Example 4 is 0.6% at the 20th cycle, and the adsorption capacity retention rate is only 15.79% after 200 cycles of lithium extraction. This is due to the lack of aluminum and cobalt doping, and the Mn of the manganese-based lithium ion sieve in the composite fiber membrane adsorbent is 3+ The disproportionation reaction and the Jahn-Teller effect intensify, resulting in the dissolution of manganese and the collapse of the crystal structure, causing the adsorption capacity to decrease rapidly with the increase in the number of cycles. The results of Example 1 and Comparative Example 5 show that without secondary calcination, no spinel structure is formed, the adsorption performance is poor, and the structure is not stable enough, and the manganese dissolution loss is high.
[0116] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A composite fiber membrane adsorbent, characterized in that: The invention comprises a polymer fiber membrane and a manganese-based lithium ion sieve-coated carbon material loaded on the polymer fiber membrane.
2. The composite fiber membrane adsorbent according to claim 1, characterized in that: The carbon material in the manganese-based lithium ion sieve coated carbon material includes carbon nanotubes; And / or, the manganese-based lithium ion sieve in the manganese-based lithium ion sieve-coated carbon material has a spinel-type crystal structure; And / or, the manganese-based lithium ion sieve in the manganese-based lithium ion sieve-coated carbon material includes a Z element, the Z element includes at least one of aluminum and cobalt, and the molar ratio of the Z element to the manganese element is 0.001-0.05:1; And / or, the polymer in the polymer fiber membrane includes at least one of polyvinyl chloride, polyvinylidene chloride and polyvinylidene fluoride.
3. A method for preparing a composite fiber membrane adsorbent according to any one of claims 1 to 2, characterized in that: The steps include: S1, dispersing the carbon material into a first acid solution for pretreatment to obtain a pretreated carbon material; a manganese source, a lithium source and a Z source undergo a hydrothermal reaction and a first calcination to obtain a manganese-based lithium ion sieve precursor; S2, mixing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent for the first time, filtering, and subjecting the obtained solid to the second calcination to obtain a manganese-based lithium ion sieve precursor-coated carbon material; S3, dispersing the manganese-based lithium ion sieve precursor coated carbon material into a polymer solution, and spinning the mixture to obtain a composite fiber membrane adsorbent precursor; S4, treating the composite fiber membrane adsorbent precursor in a second acid solution to obtain the composite fiber membrane adsorbent.
4. The preparation method according to claim 3, characterized in that: The first acid solution is a mixed solution of hydrochloric acid and sulfuric acid, and the volume ratio of the hydrochloric acid to the sulfuric acid is 1:2-5.
5. The preparation method according to claim 3, characterized in that: The first mixing includes ultrasonically dispersing the pretreated carbon material and the manganese-based lithium ion sieve precursor in a solvent respectively to obtain a pretreated carbon material suspension and a manganese-based lithium ion sieve precursor suspension, and dropping the manganese-based lithium ion sieve precursor suspension into the pretreated carbon material suspension.
6. The preparation method according to claim 3, characterized in that: The step S1 satisfies at least one of the following conditions (1) to (5): Condition (1): The pretreatment includes heating to 100°C to 130°C and stirring for 2h to 4h, followed by filtering, washing and drying; Condition (2): The Z source includes at least one of an aluminum source and a cobalt source, and the molar ratio of the Z element in the Z source to the manganese element in the manganese source is 0.001-0.05:1; Condition (3): A pore-forming agent is further added to the hydrothermal reaction, wherein the pore-forming agent comprises at least one of ammonium carbonate and ammonium bicarbonate, and the mass of the pore-forming agent accounts for 10% to 30% of the total mass of the manganese source, the lithium source and the Z source; Condition (4): The temperature of the hydrothermal reaction is 110°C to 180°C and the duration is 30h to 55h; Condition (5): The temperature of the first calcination is 400°C to 550°C, and the duration is 6h to 12h.
7. The preparation method according to claim 3, characterized in that: The step S2 satisfies at least one of the following conditions (6) to (8): Condition (6): The mass ratio of the pretreated carbon material to the manganese-based lithium ion sieve precursor is 0.1-0.6:1; Condition (7): The temperature of the second calcination is 400°C to 600°C, and the duration is 2h to 8h; Condition (8): The second calcination is carried out under a protective atmosphere.
8. The preparation method according to claim 3, characterized in that: The step S3 satisfies at least one of the following conditions (9) to (11): Condition (9): The polymer comprises at least one of polyvinyl chloride, polyvinylidene chloride and polyvinylidene fluoride, and the concentration of the polymer solution is 55 g / L to 75 g / L; Condition (10): The mass ratio of the manganese-based lithium ion sieve precursor coated carbon material to the polymer is 1:0.1-0.2; Condition (11): The spinning process further includes drying, the drying temperature is 60° C.-90° C., and the drying time is 24 h-72 h.
9. The preparation method according to claim 3, characterized in that: The second acid solution includes hydrochloric acid, and the concentration thereof is 0.1 mol / L to 0.5 mol / L.
10. Use of the composite fiber membrane adsorbent according to any one of claims 1-2 or the composite fiber membrane adsorbent obtained by the preparation method according to any one of claims 3-9 in extracting lithium from brine.